QRIS implementation benefits and risks: A phenomenological study of Sleman's culinary MSMEs - Aurelia Melinda Nisita Wardhani (Review of Management, Accounting, and Business Studies, 2024)
This study explored the benefits and risks of Quick Response Code Indonesian Standard (QRIS) adoption among culinary MSMEs in Sleman Regency, Yogyakarta. Utilizing interviews with 216 business owners, the research followed a qualitative approach with data reduction, presentation, and conclusion stages. The findings revealed that QRIS significantly enhanced operational efficiency through faster payments, ease of use, and increased consumer trust. However, financial risks, such as administrative fees and fraud, and operational risks, including system errors and network instability, posed challenges for MSMEs. These insights provided valuable guidance for MSME actors and policymakers on optimizing QRIS benefits while mitigating its risks, emphasizing the need for improved infrastructure and adjusted cost structures.